2010
DOI: 10.1038/leu.2010.226
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of the oral mTOR inhibitor everolimus in relapsed aggressive lymphoma

Abstract: The phosphatidylinositol 3-kinase signal transduction pathway members are often activated in tumor samples from patients with non-Hodgkin's lymphoma (NHL). Everolimus is an oral agent that targets the raptor mammalian target of rapamycin (mTORC1). The goal of this trial was to learn the antitumor activity and toxicity of single-agent everolimus in patients with relapsed/refractory aggressive NHL. Patients received everolimus 10 mg PO daily. Response was assessed after two and six cycles, and then every three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
217
3
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(231 citation statements)
references
References 32 publications
10
217
3
1
Order By: Relevance
“…[194][195][196] These results have been validated in early-stage clinical trials in adults, finding single-agent ORR of 28-30%, using everolimus or temsirolimus. [197,198] Hodgkin's disease is a highly curable tumor in children; however, more aggressive or relapsed Hodgkin's disease can be difficult to treat. Preclinical studies have demonstrated that AKT is often constitutively activated in Hodgkin's disease cell lines; however, no studies have confirmed or refuted this finding in primary tumors.…”
Section: Lymphomasmentioning
confidence: 99%
“…[194][195][196] These results have been validated in early-stage clinical trials in adults, finding single-agent ORR of 28-30%, using everolimus or temsirolimus. [197,198] Hodgkin's disease is a highly curable tumor in children; however, more aggressive or relapsed Hodgkin's disease can be difficult to treat. Preclinical studies have demonstrated that AKT is often constitutively activated in Hodgkin's disease cell lines; however, no studies have confirmed or refuted this finding in primary tumors.…”
Section: Lymphomasmentioning
confidence: 99%
“…Therefore we need to find markers to determine the activation level of the mTOR pathway and to predict response to mTOR inhibitor therapy in diffuse large B-cell lymphomas for the selection of patients who may further benefit from mTOR inhibition. 17,18 Materials and methods…”
mentioning
confidence: 99%
“…RAD001 binds the intracellular protein FK-506-binding protein-12, forming a complex that inhibits the activity of mTORC1, thus affecting cell cycle progression, survival, angiogenesis and glycolysis. 17 RAD001 has been shown to be active against many subsets of leukemia, such as AML and acute promyelocytic leukemia, 18 non-Hodgkin's lymphoma 19 and other hematological malignancies, being under evaluation in several phase I/II clinical trials. 20 However, B-pre ALL was not included in these trials.…”
Section: Introductionmentioning
confidence: 99%